Think globally, act locally: Case study BSU summer school in Shanghai, China 2018 - CHIEN WEN YU; JABBAR AL-OBAIDI (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This article examines the perspectives of Chinese students and faculty regarding their learning and teaching styles, intercultural understanding, and pedagogical skills. With the backdrop of declining state and federal funding for public education in the United States, competition for students, and a strong academic desire for the internationalization of higher education, universities have begun to focus on global issues to promote global citizenship among their student bodies. Bridgewater State University (BSU), a public institution of medium size, was an early adopter of signing a partnership agreement and collaborating with a third-party organization in China to recruit students.Method: Quantitative and qualitative methods were used to compile the analytical discussion analysis. This article focuses on the international educational model KAP: Knowledge, Attitudes, and Practice and how it applies to theories of interpersonal communication and the growth of communication and management.Findings: The results indicate that students across China are drawn to BSU’s summer program in Shanghai. Colleges and universities in the United States and Canada have no problem recognizing, accepting, and transferring credits earned at American institutions like Bridgewater State University and Canadian university summer programs. Implications/Novel Contribution: The significance of this case is1) To showcase the innovative approach of BSU to provide academic opportunities for international students to complete a portion of requiredand elected courses taught by BSU faculty and2) To avoid the cost of building and maintaining international campuses or branches abroad.